The effects of a single session of spinal manipulation on strength and cortical drive in athletes - Christiansen, T. L.; Niazi, I. K.; Holt, K.; Nedergaard, R. W.; Duehr, J.; Allen, K.; Marshall, P.; Türker, K. S.; Hartvigsen, J.; Haavik, H. (European Journal of Applied Physiology, 2018)
Purpose: The primary purpose of this study was to investigate whether a single session of spinal manipulation (SM) increases strength and cortical drive in the lower limb (soleus muscle) of elite Taekwondo athletes. Methods: Soleus-evoked V-waves, H-reflex and maximum voluntary contraction (MVC) of the plantar flexors were recorded from 11 elite Taekwondo athletes using a randomized controlled crossover design. Interventions were either SM or passive movement control. Outcomes were assessed at pre-intervention and at three post-intervention time periods (immediate post, post 30 min and post 60 min). A multifactorial repeated measures ANOVA was conducted to assess within and between group differences. Time and session were used as factors. A post hoc analysis was carried out, when an interactive effect was present. Significance was set at p = 0.05. Results: SM increased MVC force [F(3,30) = 5.95, p < 0.01], and V-waves [F(3,30) = 4.25, p = 0.01] over time compared to the control intervention. Between group differences were significant for all time periods (p < 0.05) except for the post60 force measurements (p = 0.07). Conclusion: A single session of SM increased muscle strength and corticospinal excitability to ankle plantar flexor muscles in elite Taekwondo athletes. The increased MVC force lasted for 30 min and the corticospinal excitability increase persisted for at least 60 min.